Fiscal rules, fiscal space and procyclical fiscal policy - Carolin Nerlich; Wolf Heinrich Reuter (European Central Bank (ECB), 2015)
In this paper we analyse the interaction of fiscal rules and fiscal space. We find strong evidence for fiscal rules being associated with higher fiscal space. Furthermore, the analysis shows that countries with more fiscal space tend to have higher discretionary expenditures, but that this effect is significantly reduced if fiscal rules are in place. A similar effect can be observed for the procyclicality of fiscal policy, which is significantly higher in an environment of ample fiscal space, while this difference is reduced with fiscal rules. Regarding the different types of fiscal rules, we find the strongest results for expenditure rules and to a lesser extent for balanced budget rules, but none for debt rules.
Keywords: E61; E62; H60; 330; discretionary fiscal policy; fiscal rules; fiscal space; procyclicality